The Effect of Animated Video Media on Improving the Listening Skills of Fifth-Grade Students at SDIT As-Sakinah in Tanjungpinang - Salsabila Rama Husniah; Amirah Amirah; Moralista Nur Hidayati; Eka Melati Putri; Addina Silmi Khairun Nisa; Wahyu Widyanto (Al-Jawhar : Journal of Arabic Language, 2025)
While listening is the absolute foundation of language acquisition, conventional, teacher-centered methods are quietly paralyzing young learners' ability to comprehend spoken Arabic, turning a vibrant living language into a dry, stagnant subject. This study aims to analyse the effect of using animated video media on listening skills in Arabic language learning among fifth-grade students at SDIT As-Sakinah in Tanjungpinang. This study employs a quantitative, quasi-experimental design with a nonequivalent control group. The study sample consists of two classes: Class V Khartoum, the experimental class, and Class V Grozny, the control class, each comprising 28 students. Data collection was conducted through tests, observations, and documentation. The main instrument was a multiple-choice test consisting of 10 items that had passed validity and reliability tests. Data analysis was performed using descriptive statistics, the Kolmogorov–Smirnov normality test, the Levene homogeneity test, and the paired-samples t-test in SPSS version 26. The study found that the experimental class’s average score increased from 66.43 on the pretest to 89.64 on the posttest, while the control class’s average score increased from 70.71 to 86.07. The results of the hypothesis test showed a significance value of 0.000 < 0.05, indicating a significant difference between the scores before and after the treatment. These findings indicate that animated video media has a positive effect on improving students’ Arabic listening skills. This study confirms that animated videos can serve as an interactive, engaging, and effective alternative learning medium to support the development of maharah al-istimā’ in Arabic language instruction at the elementary school level.